Novel perspectives for investigating congenital anomalies of the kidney and urinary tract (CAKUT) - Renkema, Kirsten; Winyard, Paul J.; Skovorodkin, Ilya N.; Levtchenko, Elena; Hindryckx, An; Jeanpierre, Cécile; Weber, Stefanie; Salomon, Rémi; Antignac, Corinne; Vainio, Seppo; Schedl, Andreas; Schaefer, Franz; et al. (Nephrology, dialysis, transplantation, 2011)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the commonest cause of chronic kidney disease in children. Structural anomalies within the CAKUT spectrum include renal agenesis, kidney hypo-/dysplasia, multicystic kidney dysplasia, duplex collecting system, posterior urethral valves and ureter abnormalities. While most CAKUT cases are sporadic, familial clustering of CAKUT is common, emphasizing a strong genetic contribution to CAKUT origin. Animal experiments demonstrate that alterations in genes crucial for kidney development can cause experimental CAKUT, while expression studies implicate mislocalization and/or aberrant levels of the encoded proteins in human CAKUT. Further insight into the pathogenesis of CAKUT will improve strategies for early diagnosis, follow-up and treatment. Here, we outline a collaborative approach to identify and characterize novel factors underlying human CAKUT. This European consortium will share the largest collection of CAKUT patients available worldwide and undertake multidisciplinary research into molecular and genetic pathogenesis, with extension into translational studies to improve long-term patient outcomes.
Gesehen am 15.09.2022